PENGARUH REBUSAN DAUN SELEDRI TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI PUSKESMAS MAMBI - Hadriyani Amin (Jurnal Kesehatan Marendeng, 2022)
Abstract. The high incidence of hypertension in the elderly and uncontrolled triggers degenerative diseases such as congestive heart failure, kidney failure and vascular disease such as stroke. The high incidence of hypertension is directly proportional to the high complications that occur, so that adequate non-pharmacological treatment is needed, one of which is celery (Apium graveolens). L) is one of the types of herbal therapy to treat hypertension. The purpose of this study was to determine the effect of boiled celery leaves on the blood pressure of the elderly with hypertension in the work area of the Mambi Public Health Center, Mamasa Regency. The research method is a quasi-experimental method, using a time series research design. This study took a sample of 20 people, the sampling technique was consecutive sampling. The measuring instrument used was an observation sheet and a sphygmanometer. Analyzed by Friedman test with a significance level of = 0.05. The results obtained by the statistical test that there was a significant difference, namely by comparing the systolic blood pressure before, 3 days of administration and 7 days of celery leaf decoction, the mean value decreased from the first, third and seventh days, namely 2.75, 2.23 and 1.03 with p value = 0.000 < 0.05, as well as Diastolic blood pressure 2.75, 1.98 and 1.30 respectively with p value = 0.000 <0.05, meaning that there is an effect of giving celery leaf decoction to reduce systolic and diastolic blood pressure.